Green Packaging in Green Supply Chain Management : A Literature Review - Saputra, Ihfadz Lucky Alfa; Yoel Santo Andrianus Sormin; Heru Prastawa; Handayani, Naniek Utami (Indonesian Green Technology Journal, 2025)
Currently, environmental issues are a widely discussed topic in the industrial world, particularly within the supply chain process. This is closely linked to the escalating environmental degradation resulting from industrial activities. Today, a healthy environment is considered an invaluable asset, and the responsibility for its preservation lies with all of us [1]. Green supply chain management (GSCM) is an approach adopted by companies to integrate environmentally friendly practices into their supply chains [2]. GSCM aims to mitigate the negative environmental impact of business operations while maintaining operational efficiency and sustainability. One crucial aspect of GSCM is the adoption of green packaging. Green packaging not only involves using environmentally friendly materials but also entails raising awareness about the necessity for a shift in packaging practices (Prakash and Pathak, 2017). This study aims to systematically review the existing literature on green packaging. The primary focus of this research is to identify trends, findings, challenges, and the latest innovations in environmentally friendly packaging and to analyze their sustainability implications.